2016
DOI: 10.5713/ajas.16.0310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Milk β-Hydroxybutyric Acid and Acetone and Their Genetic Association with Milk Production Traits of Holstein Cattle

Abstract: This study was conducted to estimate the genetic parameters of β-hydroxybutyrate (BHBA) and acetone concentration in milk by Fourier transform infrared spectroscopy along with test-day milk production traits including fat %, protein % and milk yield based on monthly samples of milk obtained as part of a routine milk recording program in Korea. Additionally, the feasibility of using such data in the official dairy cattle breeding system for selection of cows with low susceptibility of ketosis was evaluated. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…In a literature review, Pryce et al (2016) reported low heritability estimates for clinical ketosis ranging from 0.01 to 0.16. In previous studies, most of the estimates for milk and serum BHB traits are low or moderate but higher than estimates for clinical ketosis (van der Drift et al, 2012;Koeck et al, 2014;Koeck et al, 2016;Miglior et al, 2014;Lee et al, 2016). For example, in a study of Lee et al (2016) the heritability for milk BHB 30 days postpartum was 0.10 (the average heritability for the first parity was 0.08).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a literature review, Pryce et al (2016) reported low heritability estimates for clinical ketosis ranging from 0.01 to 0.16. In previous studies, most of the estimates for milk and serum BHB traits are low or moderate but higher than estimates for clinical ketosis (van der Drift et al, 2012;Koeck et al, 2014;Koeck et al, 2016;Miglior et al, 2014;Lee et al, 2016). For example, in a study of Lee et al (2016) the heritability for milk BHB 30 days postpartum was 0.10 (the average heritability for the first parity was 0.08).…”
Section: Discussionmentioning
confidence: 94%
“…Koeck et al, 2016), BHB concentration measured at first or some specific test day (e.g. van der Drift et al, 2012;Koeck et al, 2014;Lee et al, 2016) and classification based on different BHB thresholds (e.g. Miglior et al, 2014) Oetzl, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…β-hydroxybutyrate and dairy cow performance routine milk recording is not feasible because it is too expensive and time consuming, whereas MIRS allows to collect data at population level cheaply and provide routine reports to farmers for monitoring their herd. Currently, the accuracy of the developed prediction equations for BHB concentration in milk is not high enough to quantify the exact content but it has proved to be useful for screening purposes to detect cows with elevated BHB concentrations in milk (Grelet et al, 2016;Lee et al, 2016;Santschi et al, 2016). Moreover, predicted milk acetone and BHB have been used to develop models for the prediction of blood BHB from test-day milk and performance traits (Chandler et al, 2018), and the use of MIRS milk spectra has been proposed to directly predict blood BHB concentration (Belay et al, 2017a and2017b).…”
Section: Methods and Thresholds Used To Define Hyperketonemiamentioning
confidence: 99%
“…Santschi et al (2016). On the other hand, Lee et al (2016) considered cows as affected by SCK with milk BHB concentration between 0.01 and 0.20 mmol/l, and affected by CK with milk BHB concentration ⩾ 0.20 mmol/l. However, even with elevated concentrations of milk BHB, a blood test and/or a veterinary visit is necessary to help on the diagnosis of HYK.…”
Section: Referencesmentioning
confidence: 99%
“…The heritability estimate for BHB concentration was close to 0, in agreement with reports from several previous studies. Lee et al (2016), for instance, reported heritability values ranging between 0.04 and 0.17 for milk BHB in Korean Holstein cows, depending on parity and stage of lactation. Similarly, heritability values ranging between 0.07 and 0.29 were reported for milk BHB in several other studies for different breeds of cattle (van der Drift et al, 2012;Koeck et al, 2014;Penasa et al, 2015;Jamrozik et al, 2016).…”
Section: Effects Of Host Genetics and Rumen Microbiome In Milk Metabomentioning
confidence: 99%